GAME EDUKASI PUZZLE RUMAH ADAT TRADISIONAL INDONESIA BERBASIS ANDROID - Dyan Yunanto (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2021)
Puzzle games are a way or style in the process of early childhood learning that is more suitable to increase children's learning interest so that the learning process feels more fun, the problem that arises is how to introduce and educate about traditional Indonesian traditional home culture so that the younger generation can get to know and preserve traditional Indonesian culture. To overcome this problem, a game is made that can introduce and educate about traditional Indonesian traditional house culture. While the programming language used in building games is constrcut2. The results of implementation and trials conducted by researchers, it can be concluded that traditional Indonesian traditional house puzzle education games can recognize and educate indonesia's most traditional culture, especially traditional house culture.